Pengaruh Harga Diri terhadap Kemalasan Sosial pada Mahasiswa Aktif Berorganisasi - Adilah Zahra Salsabila; Theda Renanita (Universitas Ciputra Surabaya, 2026)
This study aimed to determine the effect of self-esteem among social loafing in students who were active in organizations. The method used was quantitative. The subjects of this research were 121 students who were active and had joined student organizations. The sample was collected using a non-probability sampling technique, particularly purposive sampling. Data collection used a questionnaire containing two scales, the social loafing scale and the self-esteem scale. Data analysis of this research used simple linear regression analysis. Based on the results of this study, R value=.414 and the coefficient of determination (R2)=.171 and the regression coefficient β(X)= -0.652. The results of this study indicated that self-esteem had a negative effect on social loafing among students active in organizations, with an effect size of 17.1%, while 82.9% was due to other factors.